Prevalence and pattern of breastfeeding among mothers in Al-Qassim region - Al-Ghasham, Yazeed A.; Al-Feraidi, Arwa D. (International Journal of Advances in Medicine, 2023)
Background: The objective of this study was to explore the prevalence of breastfeeding (BF) among the mothers living in the Al-Qassim region of Saudi Arabia. This study also aimed to evaluate the factors causing delayed initiation of BF. Method: This cross-sectional study was conducted between November and December 2022 in which mothers who were living in the Al-Qassim region were eligible to participate. A self-administered questionnaire was used for collecting the data which was sent electronically. Results: Out of 265 mothers participated in the study, 38.9% were 30-40 years old and over 70% were having at least bachelor’s degree. Findings revealed that 82.5% timely initiated the BF while 25.3% had exclusive BF in the initial first six months. Mothers who had cesarean delivery and those who did not complete gestational age were in significantly less in proportion of receive education about BF after delivery (p=0.034 and p=0.015 respectively). In addition, mothers having cesarean delivery had 4.13 times higher odds of delayed initiation of BF (p=0.000) and mothers who had preterm delivery had 7.76 times more likely to delay initiation of BF (p=0.027). Conclusions: Prevalence of exclusive BF for initial six months were found to be among quarter of the mothers participated in the study. It was required to increase mothers’ knowledge and to educate them before and after delivery which facilitate to increase the prevalence of BF. Delivery method and gestational age were the factors causing delayed initiation of BF hence healthcare providers are required to counter the situation to increase the prevalence.